Dynamical SEI Reinforced by Open‐Architecture MOF Film with Stereoscopic Lithiophilic Sites for High‐Performance Lithium–Metal Batteries. (28th April 2021) - Wu, Qingping; Zheng, Yongjian; Guan, Xiang; Xu, Jun; Cao, Fahai; Li, Chilin
Abstract: A vulnerable solid–electrolyte interphase (SEI) layer cannot retard Li dendrite growth, electrolyte consumption, and anode volumetric expansion, which seriously hinders the development of high‐safety Li‐metal batteries (LMBs). Herein, a dynamical SEI reinforced by an open‐architecture metal–organic framework (OA‐MOF) film characterized by elastic expansion and contraction of the volume of stereoscopic lithiophilic sites, is designed. The self‐adjustment distribution of lithiophilic sites on vertically grown Cu2 (BDC)2 nanosheets enables the homogenization of Li‐ion flux, smart control of Li mass transport, and compaction of Li deposition. The trapped N, N ‐dimethylformamide molecules in the open framework structure are favorable for the better wetting and dissolution effect of Li‐ions accessing to Cu2 (BDC)2 . Combining these advantages, the featured OA‐MOF/Cu@Li anode enables a high coulombic efficiency and low voltage hysteresis in Li||Cu cells even at an ultrahigh current density of 15 mA cm −2 . Abstract : A dynamical solid electrolyte interface reinforced by an open‐architecture metal–organic framework (OA‐MOF) film is designed. The self‐adjustment distribution of stereoscopic lithiophilic sites on vertically grown Cu2 (BDC)2 nanosheets enables the homogenization of Li‐ion flux, smart control of Li mass transport, and compaction of Li deposition. The lithiated OA‐MOF/Cu anode enables high coulombic efficiency and low voltage hysteresis even at 15 mA cm −2 .